Volatile compounds and sensory profile of suspensions of fresh and stored oat flour from batches of pure Finnish cultivars - Puganen, Anna; Damerau, Annelie; Hakanen, Sari A.; Yang, Baoru; Laaksonen, Oskar; Linderborg, Kaisa M. (Elsevier BV, 2026)
Oats are healthy and suitable for versatile food applications, yet seldomly studied as pure cultivars. Due to their high content of unsaturated lipids and required dehulling and kilning processes, lipid oxidation affects the sensory properties of oat products. In this study, twenty batches of oat flour, each from a pure cultivar grown in Finland during the same growing season, were stored for six months. Volatile compounds and sensory profiles were analyzed using an oat suspension model. The overall flavor was described as mild. The panelists could differentiate the batches based on oat, bitter, and green flavor, texture, and appearance, which correlated with volatile profiles, and contents of moisture, fiber, beta-glucan, and avenanthramides. A gas chromatographyolfactometry test of four selected flour batches revealed odor-active volatiles. Panelists could discriminate between zero- and six-month samples based on increases in odor and flavor intensity, and bitter flavor at six months linked to oxidation processes.